PENGEMBANGAN KURIKULUM 2013 SEBAGAI PEMBENTUK KARAKTER AKHLAKUL KARIMAH - Siti Aisyah (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2020)
The success of quality education development is influenced by the availability of various supporting components. One of them is a curriculum that was developed and used at the level of the education unit. Therefore, the curriculum must be developed from time to time Curriculum development is a complex process, which involves various interrelated components. Therefore, in the 2013 curriculum development process it does not only require technical skills from the developer to develop various components of the curriculum, but it must also be understood the various components that influence it. The implementation evaluations of learning Islamic Education and Characteristics in the 2013 Curriculum included attitude competency assessment, knowledge competency assessment, and skills assessment. The formation of national character is highly expected through PAI subject matter then developed in the daily lives of students at school. Character formation is carried out systematically to help students understand the values of character and human behavior related to God, self, fellow human beings, environment, and behavior, which is supported by the method of forming the right character in fostering the younger generation in Islam.